SUSTAINABLE DEVELOPMENT GOALS (SDGS) AND ITS IMPACT ON FAMILY BUSINESSES: A SCOPING REVIEW (International Journal of Innovative Technologies in Economy, 2024)
Family businesses play a crucial role in the global economy, and as such, their contribution to achieving the United Nations Sustainable Development Goals (SDGs) cannot be overstated. This article explores the impact of SDGs on family businesses and the role of family businesses in achieving the SDGs. It examines the ways in which family businesses can help to promote sustainable development through their operations, strategies, and social responsibility initiatives. The article also considers the challenges faced by family businesses in aligning with SDGs and the strategies they can adopt to overcome these challenges. The article draws on a range of academic and industry sources to provide insights into the opportunities and challenges that SDGs present to family businesses from 2012 to 2022. This article employed the scoping literature review approach. Key findings include the need for family businesses to adopt a long-term view of sustainable development, the importance of collaboration with other stakeholders, and the role of innovation in driving sustainable growth. The literature was analysed and presented, using themes. Overall, the article demonstrates that family businesses have a crucial role to play in achieving the SDGs, and that by adopting sustainable practices, they can not only contribute to the achievement of the goals, but also drive long-term growth and profitability.